The Influence of Organizational Culture on Organizational Performance with Organizational Commitment and Leadership as Mediation - Utomo, Alghani Imansyah; Tanuwijaya, Justine; Gunawan, Andreas Wahyu (Borong Newinera Publisher, 2024)
This study aims to determine the relationship between organizational culture, organizational commitment and leadership that can affect organizational performance in non-profit organizations. This research uses a quantitative approach using the PLS (Partial Least Square) based SEM (Structural Equation Model) method using SmartPLS 3.0 software. The sample in this study were employees of the Ministry of Education and Culture. The data collection technique for this research uses a questionnaire. The variables used in this study are organizational culture, organizational commitment, leadership, and organizational performance. The results of this study include organizational culture and leadership directly on organizational performance, while leadership can significantly increase the influence of organizational culture on company performance. In addition, organizational commitment is known to have no significant effect on organizational performance and cannot increase the influence of organizational culture on organizational performance. In this study, it is suggested that stakeholders for the Ministry of Education and Culture can increase their attention to factors that can affect the improvement of organizational performance, especially organizational culture and leadership.